RBL-STEM Integration in Making Eco-Enzyme from Jenggawah Market Vegetable Waste to Improve Students' Creative Thinking Skills - Komaria, Nurul; Sarwo, Danuji; Dwi, Sukamto Sucianingtyas (JURNAL BIOEDUCATION, 2025)
This study aims to overcome the problem of vegetable waste produced at Jenggawah Market by processing it into an environmentally friendly product in the form of eco-enzyme through the STEM-based Research-Based Learning (RBL) model. This study uses a qualitative descriptive approach. This approach was chosen to describe in depth the process of integrating Research-Based Learning (RBL) with the STEM (Science, Technology, Engineering, and Mathematics) approach in making eco-enzyme and its impact on student creativity. The results of the study show that the integration of RBL-STEM has great potential in equipping students to learn about vegetable waste fermentation to produce eco-enzyme. In addition, it can also foster environmental awareness. Thus, the RBL-STEM approach is worthy of being used as a contextual learning model that is applicable and provides solutions to real problems in the surrounding environment.